Study on the Political Background of Rural Women Positions in Panchayati Raj System: Examining the Political Context of Rural Women in the Panchayati Raj System (Journal of Advances and Scholarly Researches in Allied Education, 2018)
There can be two ways to deal with the examination and plan of the idea of Panchayati Raj - the standardizing and observational. The standardizing scholar might want to develop a perfect theoretical model as per his own vision and aspirafions. The empiricist on the opposite would be keen on contemplating the idea in activities, in distinguishing the hole between the perfect and the genuine, in showing the operational patterns that seem to impact or alter the idea practically speaking or even to push back new theoretical skylines lastly, in anticipating an empiricist's perspective on the emerging idea of Panchayati Raj.